Changes in the chronic and postprandial blood lipid profiles of trained competitive cyclists and triathletes following a ketogenic diet: a randomized crossover trial - Austin J. Graybeal; Andreas Kreutzer; Kamiah Moss; Meena Shah (BMC, 2024)
Abstract Background The ketogenic diet (KD) is the most popular carbohydrate restriction strategy for endurance athletes. However, because the primary goal of employing the KD is to gain a competitive advantage in competition, endurance athletes may be less concerned with the influence of the KD on their cardiometabolic health; particularly their blood lipid profiles. Thus, the purpose of this study was to examine the chronic and postprandial blood lipid alterations following a two-week ad libitum KD compared to an ad libitum high-carbohydrate diet (HCD) and the athletes' habitual diet (HD) in a group of trained competitive cyclists and triathletes. Methods Six trained competitive cyclists and triathletes (female: 4, male: 2; age: 37.2 ± 12.2) completed this randomized crossover trial, which required them to follow a two-week ad libitum KD and HCD in a randomized order after their HD. Fasting blood lipids were collected following their HD and after two-weeks of the KD and HCD conditions. Postprandial blood lipid responses to a test meal reflective of the assigned diet were collected at the end of each diet condition. Results Fasting total cholesterol (TC) was significantly higher following the KD compared to the HD (p < 0.001) and HCD (p = 0.006). Postprandial incremental area under the curve for triglycerides (TRG), TRG:HDL ratio, and VLDL-C were significantly higher following the KD test meal compared to the HD (all p < 0.001) and HCD (all p = 0.001) test meals but LDL-C and LDL:HDL ratio were significantly lower following the KD compared to the HD and HCD test meals (all p < 0.001). Conclusions Trained competitive cyclists and triathletes demonstrate increased TC in response to a two-week KD compared to a HCD or HD. Endurance athletes contemplating a KD should consider the potential for these blood lipid alterations, and future research should focus on postprandial blood lipid responses to determine if these changes manifest in chronic blood lipid shifts. Trial registration ClinicalTrials.gov Identifier: NCT04097171 (11 October 2019).